Adaptasi Novel Bumi Manusia Karya Pramoedya Ananta Toer Ke Film Bumi Manusia Sutradara Hanung Bramantyo - Jenefri Mardianti; Syafril Syafril; Ivan Adilla (Puitika, 2023)
This research was motivated by the author’s interest in the novel Bumi Manusia by Pramoedya Ananta Toer, which was previously banned, then in 2019 it was filmed with the same title, namely Bumi Manusia, directed by Hanung Bramantyo. The activity of adapting a novel to a film will cause a change. These changes concern a number of ideological elements in each work. This research discusses how the ideology of the novel Bumi Manusia by Pramoedya Ananta Toer was adapted to the film Bumi Manusia directed by Hanung Bramantyo. This research objective  to explain how the ideological adaptation of the novel Bumi Manusia by Pramoedya Ananta Toer was adapted to the film Bumi Manusia directed by Hanung Bramantyo. This research was conducted using Linda Hutcheon's theory. This theory is used to discover and explain story adaptations and ideological adaptations from novels and films. This research uses qualitative methods by obtaining written data from both novel and film media that refer to social problems. The techniques used are data collection, data analysis, and presentation of data analysis results.From the research carried out, it was concluded that in the adaptation of the novel Bumi Manusia to the film Bumi Manusia, changes occurred which included reducing and adding characters, eliminating several events, changing the setting and storyline. Meanwhile, the ideological adaptation is that the novel Bumi Manusia is based on political and social ideology, while the film Bumi Manusia is based on economic ideology.